Association of gestational diabetes mellitus with vitamin D deficiency among Saudi pregnant women: A case-control study (Journal of Fatima Jinnah Medical University, 2019)
Background: Prevalence of gestational diabetes mellitus (GDM) and 25-hydroxyvitamin D (vitamin D) deficiency is high in Saudi Arabia. Whether GDM is associated with low vitamin D level or not is still under debate, and the literature regarding this association is deficient in Saudi Arabia. GDM is associated with an adverse pregnancy outcome; therefore, the current study was conducted on Saudi pregnant women to evaluate this relationship.Subjects and methods: This case-control study was conducted in the antenatal clinic at King Fahad Medical City, Riyadh, from February 2015 till February 2017. The Study included 300 pregnant women, of which 100 were GDM cases, and 200 were controls (i.e., without GDM). Cases and control were matched for age, parity, body mass index, gestational age, family history of diabetes mellitus. Vitamin D levels were obtained between 24 to 28 weeks of gestation along with Oral Glucose Tolerance Test (OGTT).Results: The levels of vitamin D among pregnant Saudi women were sufficient in 13%, insufficient in 51%, and deficient in 36%. It was evident that Vitamin D deficiency (
Keywords: Gestational diabetes mellitus; 25-hydroxyvitmain D; Pregnant